The Effectiveness of CALL-Based Quizizz in Improving Students’ Arabic Listening Skills - Aghnia Zahra Ramadhani; Haeruddin Haeruddin; Haeriyyah Haeriyyah; Zuhriah Zuhriah (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The low level of Arabic listening skills among elementary school students remains a persistent issue due to the dominance of conventional teaching methods that provide limited interaction and feedback. This study aims to analyze and evaluate the effectiveness of Quizizz Paper Mode based on Computer-Assisted Language Learning (CALL) in improving students’ Arabic listening skills. This study employed a quantitative approach using a one-group pretest–posttest design. The research subjects consisted of 22 fifth-grade students selected as the experimental group. Data were collected through listening comprehension tests administered during the pretest and posttest stages, as well as a Likert-scale questionnaire to examine students’ perceptions of the learning media used. The primary research instrument was a listening test integrated with Quizizz Paper Mode using Q-Card. Data were analyzed using descriptive statistical techniques. The results indicate that the implementation of Quizizz Paper Mode significantly improved students’ listening skills and increased their engagement during the learning process. Students also demonstrated positive perceptions regarding comprehension, motivation, and the ease of use of the learning media. These findings suggest that Quizizz Paper Mode serves as an effective and interactive learning medium for strengthening Arabic listening skills at the elementary school level. The study implies that the integration of gamification with a Computer-Assisted Language Learning (CALL) approach can support more engaging listening instruction and provide practical guidance for teachers in developing interactive language learning environments.